Student Assessment as a Political Construction: The Case of Uruguay - Benveniste, Luis (Education Policy Analysis Archives, 2000)
This article reveals the interplay between assessment policies in Uruguay and the nature of State-societal relations. The central State has been historically a staunch defender of public education and has championed the cause of equalizing opportunities for the most disadvantaged sectors of society. The national evaluation system of student performance has been constructed as an expression of this tradition. The Uruguayan government sought to build a wide level of consensus with respect to the assessment instruments by encouraging educators to participate and buy into the assessment initiative. Moreover, the national government shifted the focus of the national evaluation from measuring schooling outcomes to addressing the social wants that condition student learning. Hence, the national evaluation has come to symbolize an agreed-upon mechanism of social accountability by which the central government upholds its responsibility for educational provision as it intervenes on behalf of impoverished communities. (Note 1)